The Impact of Social Media on Self-Identity and Interaction Generation Z in Indonesia - Merly Serla Marlena; Roviul Huda; Abdul Aziz; Sulistio Sulistio; Ali Murtadho (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study examines the influence of social media on the formation of self-identity and interaction patterns among Generation Z in Indonesia using a qualitative approach through a literature review. As a generation that has grown up in a digital ecosystem, Generation Z views social media as an integral part of daily life whether for communication, self-expression, or building a self-image. The findings reveal that social media plays a dual role. On one hand, it serves as a space for self-expression, self-exploration, expanding social networks, and a means of obtaining emotional support from online communities. On the other hand, social media also creates social pressure through a culture of comparison, unrealistic beauty standards, and a tendency to form identities that are out of sync with one’s true self. Excessive use of social media also affects interaction patterns, particularly the decline in the quality of face-to-face communication, reduced empathy, and the rise of brief, instant, and symbolic communication patterns. Research findings also indicate that algorithms, curated content, filter bubbles, digital ads, and the influence of virtual communities are key factors shaping Generation Z’s self-perception and interaction behaviors. In addition, heavy use of social media can have an impact on mental health, leading to anxiety, low self-esteem, and dissatisfaction with oneself. Therefore, digital literacy, self-control, and educational guidance are necessary to ensure that Generation Z can use social media wisely and in a balanced way. In this way, social media can serve as a valuable tool without compromising the quality of one’s self-identity and real-world social relationships.